Understanding the human dimensions of a sustainable energy transition - Steg, Linda; Perlaviciute, Goda; van der Werff, Ellen (Frontiers in Psychology, 2015)
Global climate change threatens the health, economic prospects, and basic food and water sources of people. A wide range of changes in household energy behaviour is needed to realise a sustainable energy transition. We propose a general framework to understand and encourage sustainable energy behaviours, comprising four key issues. First, we need to identify which behaviours need to be changed. A sustainable energy transition involves changes in a wide range of energy behaviours, including the adoption of sustainable energy sources and energy-efficient technology, investments in energy efficiency measures in buildings, and changes in direct and indirect energy use behaviour. Second, we need to understand which factors underlie these different types of sustainable energy behaviours. We discuss three main factors that influence sustainable energy behaviours: knowledge, motivations, and contextual factors. Third, we need to test the effects of interventions aimed to promote sustainable energy behaviours. Interventions can be aimed at changing the actual costs and benefits of behaviour, or at changing people’s perceptions and evaluations of different costs and benefits of behavioural options. Fourth, it is important to understand which factors affect the acceptability of energy policies and energy systems changes. We discuss important findings from psychological studies on these four topics, and propose a research agenda to further explore these topics. We emphasise the need of an integrated approach in studying the human dimensions of a sustainable energy transition that increases our understanding of which general factors affect a wide range of energy behaviours as well as the acceptability of different energy policies and energy system changes.